2008
DOI: 10.1177/0734242x07081481
|View full text |Cite
|
Sign up to set email alerts
|

Report: Medical students for monitoring biomedical waste segregation practices — why and how? Experience from a medical college

Abstract: The cornerstone for an effective biomedical waste (BMW) management is appropriate waste segregation. Improper waste segregation practices can have an adverse impact on public health and increase the cost of treatment. Deficiencies in waste segregation practices can be corrected by continuous monitoring and education. Manpower for monitoring waste segregation in a large teaching hospital is scanty. We utilized the undergraduate medical students as monitors and studied the impact on waste segregation practices. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…Research has been done on programs that focus on how to appropriately separate waste materials. Hagen et al 26 conducted a study on an HCW management education and training program for health care workers in Saudi Arabia, while Nataraj et al 27 focused on how waste materials were separated and discarded at a medical school in India. The results of both studies were more promising than ours; however, comparing these studies is difficult because the target group of the first one was hospital employees with stable jobs as opposed to dental students, who could overlook the mandatory need for these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Research has been done on programs that focus on how to appropriately separate waste materials. Hagen et al 26 conducted a study on an HCW management education and training program for health care workers in Saudi Arabia, while Nataraj et al 27 focused on how waste materials were separated and discarded at a medical school in India. The results of both studies were more promising than ours; however, comparing these studies is difficult because the target group of the first one was hospital employees with stable jobs as opposed to dental students, who could overlook the mandatory need for these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…High score for 'segregation of waste' (96%) shows that this fundamentalpart of waste management was being properlyattended. In a study in a tertiary care hospital in Mumbai [10], it was found that waste segregation was less than 40% which was unsatisfactory. In studies conducted in Egypt [11] and Ethiopia [12], the waste segregation practices were found to be poor.…”
Section: Resultsmentioning
confidence: 99%
“…7 Another study conducted by Natraj et al showed results indicating that a statistically significant improvement in waste segregation practices occurred with a prospective study of 6 months duration from August 2004 to January 2005. 4 A study conducted by Kumar et al with a follow up after 18 months post intervention it was found that participants had statistically significantly (p<0.05) better knowledge. 12 Another study conducted by Elnour et al in Sudan showed that the participants had knowledge regarding HCW management as 17% good, 58% fair, and 25% poor before the educational intervention program.…”
Section: Discussionmentioning
confidence: 96%
“…Improper segregation can pose an adverse impact on public health and thus increase the cost of treatment. 4 Meticulous and scientific disposal of biomedical waste is important and if not done then this waste by healthcare institutions can contribute to the spread of contagious diseases like hepatitis and AIDS (HIV) among those who manually handle it and also among the general public. 5 Appropriate knowledge of health care waste management among the interns is the first step towards developing favourable attitude and practices.…”
Section: Introductionmentioning
confidence: 99%